Geographic variation in daily temporal activity patterns of a neotropical marsupial (Gracilinanus agilis) - Vieira, Emerson M.; De Camargo, Nícholas F.; Colas, Paul F. [UNESP]; Ribeiro, Juliana F.; Cruz-Neto, Ariovaldo P. [UNESP] (Public Library of Science (PLoS), 2017)
The temporal activity of animals is an outcome of both biotic and abiotic factors, which may vary along the geographic range of the species. Therefore, studies conducted with a species in different localities with distinct features could elucidate how animals deal with such factors. In this study, we used live traps equipped with timing devices to investigate the temporal activity patterns of the didelphid Gracilinanus agilis in two dry-woodland areas of the Brazilian savanna (Cerrado). These areas were located about 660 km apart, one in Central Brazil and the other in Southeastern Brazil. We compared such patterns considering both reproductive and non-reproductive periods, and how it varies as a function of temperature on a seasonal basis. In Central Brazil, we found a constant, and temperature-independent activity during the night in both reproductive and non-reproductive periods. On the other hand, in Southeastern Brazil, we detected a constant activity during the reproductive period, but in the non-reproductive period G. agilis presented a peak of activity between two and four hours after sunset. Moreover, in this latter we found a relation between temporal activity and temperature during the autumn and spring. These differences in temporal activity between areas, observed during the non-reproductive period, might be associated with the higher seasonal variability in temperature, and lower mean temperatures in the Southeastern site in comparison to the Central one. In Southeastern Brazil, the decrease in temperature during the non-reproductive season possibly forced G. agilis to be active only at certain hours of the night. However, likely due to the reproductive activities (intensive foraging and searching for mates) this marsupial showed constant, temperature-independent activity during the night in the reproductive period at both sites.